Rekrutmen Calon Kepala Daerah Partai Golkar pada Pemilukada Padangsidimpuan - RYAN RIZKY ARIFIN HARAHAP (Universitas Sumatera Utara, 2014)
Regional election is an important process in Indonesia as a democratic state. In 2012 elections held in the Kota Padangsidimpuan. Essentially political parties become the main motor in the local election and it did happen in this case. Golkar party is the party that lead the prospective regional head. The result of this process is Chaidir Ritonga as the candidate from the Golkar Party and He would pairs with Mara Gunung Harahap. This is a study about Golkar Party’s (Partai Golkar) candidates recruitment mechanism the regional head in local election of Pa-dangsidimpuan 2012. The focus mainly disscusses about how the regional head candidates re-cruitment’s process from Golkar Party in Padangsidimpuan 2012 local election. This research used descriptive methods, using observations, interviews and literature. This study detected three important things in recruitment process: First, inventory figure names that considered able to leading Padangsidimpuan City; Second, survey and selection stage; Third, determina-tion of the head regional candidates.Keywords: local election, candidates recruitment.